Diagnosis of narrow‐band imaging in non‐muscle‐invasive bladder cancer: A systematic review and meta‐analysis. (1st November 2012) - Li, Kaiwen; Lin, Tianxin; Fan, Xinxiang; Duan, Yu; Huang, Jian
<x xml:space="preserve">Abstract</x> Objectives The objective was to evaluate the diagnostic accuracy of cystoscopy assisted by narrow‐band imaging compared with white‐light imaging for non‐muscle‐invasive bladder cancer. Methods An electronic database search of PubMed, Embase, the Cochrane Library, Ovid and Web of Science was carried out for all articles comparing narrow‐band imaging with white‐light imaging cystoscopy in the detection of non‐muscle‐invasive bladder cancer. The review process followed the guidelines of the Cochrane Collaboration. Results Seven studies with prospectively collected data including a total of 1040 patients were identified, and 611 patients with 1476 tumors were detected by biopsy. In the patient‐ and tumor‐level analysis, an additional 17% of patients (95% confidence interval, 10–25%) and an additional 24% of tumors (95% confidence interval, 17–31%) were detected by narrow‐band imaging, respectively. In the patient‐ and tumor‐level analysis, significantly higher detection rates using narrow‐band imaging (rate difference 11%; 95% confidence interval 5–17%; P < 0.001; and rate difference 19%; 95% confidence interval 12–26%; P < 0.001, respectively) rather than white‐light imaging were found. On the tumor level, an additional 28% of carcinoma in situ was detected (95% confidence interval 14–45%) by narrow‐band imaging, and a significantly higher detection rate (rate difference 11%; 95% confidence interval 1–21%; P = 0.03) was found. The false‐positive detection rate of tumor level did not differ significantly between the two techniques. Conclusions Cystoscopy assisted by narrow‐band imaging detects more patients and tumors of non‐muscle‐invasive bladder cancer than white‐light imaging, and it might be an additional or alternative diagnostic technique for non‐muscle‐invasive bladder cancer.